Evaluation of sports tourism competitiveness of urban agglomerations in Guangdong-Hong Kong-Macao Greater Bay Area - Jie Tian; Wanjin Deng; Jun Yuan (Heliyon, 2023)
In the era of experience economy, sports tourism has been emerged as a new tourism form and consumption hot spot. Evaluation of the competitiveness of sports tourism is helpful to accurately grasp the key competitive factors of sports tourism development and enhance regional sports tourism resource development, market expansion and product upgrading. This study adopted entropy-weight TOPSIS model to construct the index system of sports tourism competitiveness of urban agglomerations and investigated the sports tourism competitiveness of 11 cities in Guangdong-Hong Kong-Macao Greater Bay Area from 2016 to 2020. The obtained results showed that sports tourism development in the Greater Bay Area was unbalanced and obviously different. Guangzhou, Shenzhen and Hong Kong are competitive, Macao is average competitive and Dongguan, Jiangmen, Zhuhai, Foshan, Zhongshan, Huizhou and Zhaoqing are less competitive. Based on evolution trend, sports tourism competitiveness in Guangzhou has always been at the forefront of the Greater Bay Area, while those of Hong Kong and Macao have presented a declining trend. Also, sports tourism competitiveness in inland cities has been continuously enhanced and the development focus of sports tourism in Guangdong-Hong Kong-Macao Greater Bay Area has gradually shifted to mainland. The 11 cities of the Greater Bay Area were classified as strong, average and weak areas on the basis of their sports tourism competitiveness scores. Finally, in terms of the overall situation of Guangdong-Hong Kong-Macao Greater Bay Area and specific conditions of various cities, countermeasures and suggestions have been provided for sports tourism resource development, sports tourism service level, government functional departments, event brand building, enterprise integration, etc.